2014
DOI: 10.1136/annrheumdis-2014-eular.1996
|View full text |Cite
|
Sign up to set email alerts
|

OP0067 Pregnancy Outcomes after Exposure to Certolizumab Pegol: Updated Results from Safety Surveillance

Abstract: Background Certolizumab pegol (CZP) is a PEGylated Fc-free anti-TNF approved in 45 countries for the treatment of rheumatoid arthritis (RA) and/or Crohn's disease (CD); it was recently approved by the EMA for psoriatic arthritis (PsA) and axial spondyloarthritis (axSpA). Analysis of pregnancy data from the UCB Pharma global safety database through 06 March 2012 has been published previously.1 Objectives To provide an updated analysis of pregnancy outcomes in rheumatic patients (pts) after CZP exposure, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 0 publications
4
70
0
6
Order By: Relevance
“…However, users of these medications trended toward a greater likelihood of reporting that a physician had told them not to have (more) children (23% vs 12% of nonusers) or were more likely to express concerns about the effects of their medications on a developing fetus (71% vs 55% of nonusers). TNF‐alpha inhibitors are currently considered to be compatible with pregnancy .…”
Section: Resultsmentioning
confidence: 99%
“…However, users of these medications trended toward a greater likelihood of reporting that a physician had told them not to have (more) children (23% vs 12% of nonusers) or were more likely to express concerns about the effects of their medications on a developing fetus (71% vs 55% of nonusers). TNF‐alpha inhibitors are currently considered to be compatible with pregnancy .…”
Section: Resultsmentioning
confidence: 99%
“…Clowse и соавт. [30]. Он содержал обновленный анализ результатов по беременности при ревма-тических заболеваниях на фоне лечения ЦЗП, с акцентом на РА.…”
Section: длительность сохранения эффек та генно-инженерных биологичесunclassified
“…That study also found an even higher rate of birth defects in babies born to women with chronic inflammatory diseases exposed to a TNFi agent than in babies born to women with chronic inflammatory diseases not receiving a TNFi agent (6.3% versus 4.7%), but the difference was not significant . The study of CZP by Clowse et al had a very low rate of congenital abnormalities (1.7%), but there was no comparison group and the thoroughness of the reporting is variable compared to a population study .…”
Section: Data On Tnfi Exposure In Pregnancymentioning
confidence: 90%
“…However, the findings provide reassurance that many pregnancies have been exposed to CZP, and where results are known, there is no clear signal of fetal harm. The study by Clowse et al does raise many issues of interpretation of maternal drug exposure in rheumatic diseases such as RA . The generalizability of these findings to other TNFi agents is unknown, partially because of the lack of late active placental transfer of CZP due to its unique structure .…”
Section: Data On Tnfi Exposure In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation